National survey of mental health and life satisfaction of gig workers: the role of loneliness and financial precarity - Adam Coutts; Senhu Wang; Lambert Zixin Li (BMJ Open)
Objectives To compare the mental health and life satisfaction of those employed in the gig work and contingent work with those in full-time or part-time work and the unemployed in the UK during the COVID-19 pandemic. To explore the possible mechanisms of latent and manifest benefits of employment, such as financial precarity and loneliness.Design Cross-sectional survey.Participants A representative sample of 17 722 employed and unemployed British adults, including 429 gig workers. People with disability, retirees and full-time students are not included in the sample.Main outcome measures Mental health (General Health Questionnaire-12 score) and life satisfaction (a direct question from UK Household Longitudinal Study (UKHLS)) as outcomes. Self-reported loneliness (four widely used questions from UKHLS) and financial precarity (a direct question from UKHLS) as mediators.Results Gig workers reported mental health and life satisfaction worse than those employed full time and part time, but better than the unemployed. Mediation analyses showed that gig workers’ worse mental health and life satisfaction than other workers were explained by their higher levels of loneliness and financial precarity, while gig workers’ better mental health and life satisfaction than the unemployed were explained by their less financial precarity.Conclusions Informal and freelance economy provided manifest benefits of employment to gig workers compared with unemployment but lacked latent benefits of employment. Public policies should provide social support to freelance and contingent workers to reduce their loneliness and improve their psychological well-being, especially during the COVID-19 pandemic.